IMPACT OF DIRECTORS AGE AND GENDER ON FIRMS’ PERFORMANCE: A CASE OF NON-FINANCIAL FIRMS LISTED ON PAKISTAN STOCK EXCHANGE - Faiz Ur Rehman; Dr. Akmal Shahzad Butt (International Journal of Contemporary Issues in Social Sciences, 2023)
This research was taken to comprehend any relation between director age (DA), firm performance (FP) and board diversity (BD). The research was taken on non-financial firms listed on PSX. Data was collected from 136 firms and 637 observations from the period of 2018-2022. Panel data and random effect model techniques were used to analyze data. The findings showed a significant relation among DA, BD and FP in non-financial firms. Person correlation revealed significant relationship between FP, DA and DB, as well as a negative relationship between DA and BD. The conclusion and future research form the last part of the paper.